Particle trapping and manipulation using hollow beam with tunable size generated by thermal nonlinear optical effect. (9th April 2018) - He, Bo; Cheng, Xuemei; Zhang, Hui; Chen, Haowei; Zhang, Qian; Ren, Zhaoyu; Ding, Shan; Bai, Jintao
Abstract: We report micron-sized particle trapping and manipulation using a hollow beam of tunable size, which was generated by cross-phase modulation via the thermal nonlinear optical effect in an ethanol medium. The results demonstrated that the particle can be trapped stably in air for hours and manipulated in millimeter range with micrometer-level accuracy by modulating the size of the hollow beam. The merits of flexibility in tuning the beam size and simplicity in operation give this method great potential for the in situ study of individual particles in air.